Systematic Literature Review: Principal’s Strategy in Managing Teacher Resources to Improve the Quality of Education - Amalia, Suci (PPSDP International Journal of Education, 2025)
This study aims to systematically examine the principal’s strategy in managing teacher resources to improve the quality of education. The principal has a strategic role in creating an effective learning environment through directed leadership. This study uses the Systematic Literature Review (SLR) method with a qualitative approach, analyzing 15 relevant scientific articles in the last ten years. The results of the study indicate that commonly applied strategies include teacher needs planning, ongoing training, academic supervision, participatory empowerment, and the creation of a conducive work climate. Transformational and collaborative leadership styles have proven effective in improving teacher performance and motivation. These findings indicate that optimal teacher resource management has a direct impact on the quality of learning and student learning outcomes. However, most of the literature is still limited to the local context and is descriptive in nature, so further research is needed with a quantitative or mixed approach to strengthen the validity and generalization of the results.